Management of Persistent Cough in Post-Covid Scenario (Homoeopathy for All, 2023)
The last few years have shown  us a phase of a difficult pandemic  called Covid. Observing the  ongoing situation, it is difficult  to say whether the pandemic has  even ended! Covid-19 is caused by  the SARS-CoV-2 virus. Affecting  the respiratory organs at large, it  produces symptoms like cold, flu,  pneumonia, breathlessness, etc.  Even after the pandemic receded,  patients reportedly suffered from  respiratory troubles in the post-covid  phase. Out of all these symptoms,  cough is one of the most common  manifestations of post-covid  syndrome. When this particular  cough is acute in nature, it is easy  to cure and is self-limited. However,  the cough becoming chronic in  nature (lasting for more than 8  weeks) is the real struggle. These  days, physicians treating patients  with persisting coughs obtain a  history of the pandemic associated  with the recurrence of cough. The  patient complaints of not being  well ever since being down with  the attack of Covid. This is what a  homeopath may link as the – ‘Never  well since syndrome’.  As the patients stopped  responding to the frequently used  medications, homeopathy can offer a  number of choices for the same. With  the help of homeopathic medicines,  the intensity and duration of cough  can be reduced to a remarkable  effect without leading to any adverse  effects. This article focuses on the  various homeopathic remedies that  can be used to alleviate persisting  cough inhibiting its recurrence.
Keywords: syndrome; manifestations; recurrence.